2005
DOI: 10.1039/b505530j
|View full text |Cite
|
Sign up to set email alerts
|

Reductive activation of nitrate reductases

Abstract: Protein film voltammetry of Paracoccus pantotrophus respiratory nitrate reductase (NarGH) and Synechococcus elongatus assimilatory nitrate reductase (NarB) shows that reductive activation of these enzymes may be required before steady state catalysis is observed. For NarGH complementary spectroscopic studies suggest a structural context for the activation. Catalytic protein film voltammetry at a range of temperatures has allowed quantitation of the activation energies for nitrate reduction. For NarGH with an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 27 publications
6
45
1
Order By: Relevance
“…Although the kinetics of the reaction cannot be evaluated in these conditions, the Mo(V) species obtained under these conditions originate from the conversion of nitrate to nitrite and hence can be considered catalytically relevant as they are produced after reoxidation by nitrate. The dithionite-reduced samples show no signal associated with Mo(V) ions, indicating that all the molybdenum is reduced to Mo(IV), in agreement with the midpoint redox potential of the Mo(V/IV) redox couple reported for other Nars [45,52]. The spectra obtained after 6 min of nitrate addition at both pH values are shown in Fig.…”
Section: Typical Of [3fe-4s]supporting
confidence: 71%
See 1 more Smart Citation
“…Although the kinetics of the reaction cannot be evaluated in these conditions, the Mo(V) species obtained under these conditions originate from the conversion of nitrate to nitrite and hence can be considered catalytically relevant as they are produced after reoxidation by nitrate. The dithionite-reduced samples show no signal associated with Mo(V) ions, indicating that all the molybdenum is reduced to Mo(IV), in agreement with the midpoint redox potential of the Mo(V/IV) redox couple reported for other Nars [45,52]. The spectra obtained after 6 min of nitrate addition at both pH values are shown in Fig.…”
Section: Typical Of [3fe-4s]supporting
confidence: 71%
“…7a is a simulation of this signal; EPR parameters in Table 3) is identical in both the as-isolated and the D 2 Oexchanged sample, suggesting that there are no solventexchangeable protons near the Mo(V) ion. The rhombic signal species has not been observed in the closely related nitrate reductases from E. coli [18], P. aeruginosa [9], P. stutzeri [12], and Paracoccus pantotrophus [52]. Spin quantification of the whole signal at pH 6 yields values that are approximately constant with time, with values close to 10% of the total molybdenum, but the ratio between components is not constant.…”
Section: Typical Of [3fe-4s]mentioning
confidence: 90%
“…Activation energies for nitrate reduction by NarGH and Nas are ca. 37 and 12 kJ mol À1 , respectively, 70 and similar values describe Fig. 9 Comparison of the activity-potential relationships displayed by NapAB (black) and W-substituted NapAB (red).…”
Section: Electrochemical Potential As a Determinant Of Electron Flux supporting
confidence: 62%
“…In the former case this may afford insight into the mechanisms of metallocofactor assembly and protection against O 2 damage. 70,74,75 It is also stimulating to see PFE expanding rapidly to provide fresh insight into integral membrane proteins incorporated within electrode supported bilayers that may be synthetic or part of living cells. 76,77 Thus, we are confident that PFE will continue to inform and stimulate studies of redox proteins for some time to come.…”
Section: Closing Remarksmentioning
confidence: 99%
“…Similar ideas were entertained to explain different affinities of the Mo center to nitrate and sulfate in a related molybdenum enzyme, nitrate reductase. 11,12 To complicate the situation, a recent EXAFS investigation of the human R160Q mutant of SO suggested that, in R160Q, the glutamine 160 coordinates to the (sixth) axial position of the Mo center, trans to the oxo ligand. 13 However, no correlation between the proposed structural modification and the pathological consequences was explicitly discussed in that study.…”
Section: Introductionmentioning
confidence: 99%